2012
DOI: 10.1097/acm.0b013e31826cf4fb
|View full text |Cite
|
Sign up to set email alerts
|

An Environmental Scan of Faculty Diversity Programs at U.S. Medical Schools

Abstract: Less than a third of medical schools had programs targeting underrepresented minority (URM) faculty, and those programs that existed differed in scope and goals. These findings suggest that a lack of resources and a preference for programs that target all faculty may limit the development of programs targeting URM faculty. Future research should examine whether diversity programs contribute to URM faculty recruitment and retention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 19 publications
0
26
0
Order By: Relevance
“…More recently in 2012, we reported on the availability and characteristics of minority faculty development programs. 15 We found that few schools (29%) have such programs and that program availability is likely a reflection of resources and a preference to establish stand-alone programs targeted to underrepresented minority faculty. To our knowledge, no previous study has examined the relationship between minority faculty development programs and underrepresented minority faculty representation, recruitment, and promotion.…”
Section: Discussionmentioning
confidence: 96%
“…More recently in 2012, we reported on the availability and characteristics of minority faculty development programs. 15 We found that few schools (29%) have such programs and that program availability is likely a reflection of resources and a preference to establish stand-alone programs targeted to underrepresented minority faculty. To our knowledge, no previous study has examined the relationship between minority faculty development programs and underrepresented minority faculty representation, recruitment, and promotion.…”
Section: Discussionmentioning
confidence: 96%
“…6 CEED has also been recognized with the University of Pittsburgh Chancellor's Affirmative Action Award. 11 The literature describes other programs designed to promote URB faculty development and recruitment in biomedical research, 2,4,[12][13][14][15][16][17][18][19] and includes at least one program in which developers noted participation was tied to enhanced inclusion, although there was no specific intent to achieve this outcome. 20 In those designed specifically for URB participants, most reported on the availability and characteristics of their programs, and evaluated their programs on the basis of the number of grant applications and manuscripts produced or satisfaction with program content.…”
Section: Discussionmentioning
confidence: 99%
“…Programs designed to prepare early-career researchers from underrepresented backgrounds 1 (URB) for academia are increasingly common, with a 2012 environmental scan documenting their presence at 29% of 124 MD-degree-granting medical schools. 2 The importance of fostering the careers of fledgling URB biomedical researchers is especially important in light of the national and local scarcity of URB scientists in biomedical research. [3][4][5][6] The Career Education and Enhancement for Health Care Research Diversity (CEED) program at the University of Pittsburgh Institute for Clinical Research Education (ICRE) is a purposefully designed program of multi-level mentoring, targeted coursework, monthly seminar series, and networking opportunities designed to promote success in academic research for URB biomedical researchers.…”
Section: Introductionmentioning
confidence: 99%
“…There have been efforts at other institutions to ensure that URB researchers within the pipeline flourish [ 11 , 17 , 18 ]. However, few programs have offered the combination of research training, career development training, mentorship, networking, and peer support that we think is critical for success.…”
Section: Discussionmentioning
confidence: 99%